Pathogenesis of primary inflammatory myopathies - Benveniste, O; Squier, W; Boyer, O; Hilton-Jones, D; Herson, S (2004)
Common elements: Primary inflammatory myopathies consist of dermatomyositis (DM), polymyositis (PM) and inclusion body myositis (IBM). They have certain characteristics in common: progressive muscle weakness and mononuclear inflammatory infiltrates in the muscle. Different mechanisms: They may be distinguished by their histological features which also reflect their different underlying pathogeneses. The mechanism of DM would be complement-mediated microangiopathy, the inflammatory infiltrate of which would be secondary to ischemic phenomena, whereas in PM the muscle fibres are damaged by cytotoxic CD8 T lymphocytes. The factors triggering-off these two forms of myositis remain unknown. IBM may be a degenerative disease with accumulation of a variety of proteins within the fibres. The inflammatory infiltrate, which is similar to that seen in PM, may be a reaction to accumulated proteins.